Increased biosynthesis and accumulation of cholesterol in maternal plasma, but not amniotic fluid in pre-eclampsia - Lee, Seung Mi (Sci Rep, 2019)
Preeclampsia is one of the most serious complications during pregnancy, defined as development of hypertension during late pregnancy affecting other organ systems (proteinuria, thrombocytopenia, renal insufficiency, liver involvement, cerebral symptoms or pulmonary edema). Preeclampsia is known to be associated with significant dyslipidemia, but the cause or mechanism of this metabolic aberration is not clear. Quantitative analysis of cholesterol precursors and metabolites can reveal metabolic signatures of cholesterol, and provide insight into cholesterol biosynthetic and degradation pathways. We undertook this study to compare the metabolic signatures of cholesterol in serum and amniotic fluid collected from women who delivered in the late preterm period. Matching serum and amniotic fluid samples were collected from women who delivered in the late preterm period (34-0/7–36-6/7 weeks), had undergone amniocentesis within 3 days of delivery, had no evidence of rupture of membranes or intra-amniotic infection/inflammation, and who had not received antenatal corticosteroid prior to amniocentesis. Patients were classified into 3 groups according to the etiology of their preterm birth: Group 1, preeclampsia; Group 2, spontaneous preterm labor; Group 3, other maternal medical indications for iatrogenic preterm birth. Quantitative metabolite profiling of cholesterols was performed using gas chromatography-mass spectrometry. A total of 39 women were included in the analysis (n = 14 in Group 1, n = 16 in Group 2, n = 9 in Group 3). In maternal blood, patients in Group 1 had significantly higher ratios of cholesterol/desmosterol and cholesterol/7-dehydrocholesterol (which represent 24- and 7-reductase enzyme activity, respectively) than those in Group 3 (p < 0.05 for each), which suggests increased cholesterol biosynthesis. In contrast, patients in Group 1 had significantly decreased ratios of individual cholesterol esters/cholesterol and total cholesterol esters/cholesterol than those in Groups 3 (p < 0.01 for each), suggesting increased reverse cholesterol transport. No differences in cholesterol ratios were found in amniotic fluid among the 3 groups. In conclusion, the metabolic signatures of cholesterol suggest increased cholesterol biosynthesis and accumulation in the maternal blood (but not amniotic fluid) of women with preeclampsia.